PRODUCT DEVELOPMENT BASED ON CUSTOMER PREFERENCES (The Indonesian Journal of Business Administration, 2019)
Indonesia itself clothing who produce streetwear motorbike fashion began to appear. Rawtype Riot is a company engaged in Streetwear motorbikers fashion based on Bandung, was founded in 2017 by art paint designer who formerly worked in Unionwell as designer profession Decky Sastra. At the end of 2018, Rawtype Riot developed sukajan’s jacket type. Even though, the sales volume of sukajan jacket had a gap with another type of issue such a versity jacket. Purpose of this study, Rawtype Riot wants to know consumer’s perceptions about the jacket so that in the development of the next jacket in accordance with the preferences of consumers and stick on the positioning of Rawtype Riot itself. To solve this issues, thid research was conducted by exploratory research to find out perception and pereference of Rawtype Riot’s customer. In exploratory research design, the researcher’s ideas and thoughts are key as it is primarily dependent on their personal inclination about a particular topic. Result of this study indicate that Rawtype Riot’s current customer obtained Exclusive brand, manly apparel, local brand and custom culture while investigating about rawtype Riot Brand, then followed to quality, the result is comfortable, durability and safety when indicate prefered jacket. Oranament design also can be variable to drive customer purchasing decision which is raw design style, vintage design, motorbike design is their prefered when see sukajan jacket while origin jacket sukajan which is oriental design avoided by customers. The last is color variable which is this informant suggested that dark and variation is consideration when preference about sukajan jacket. Conclusion of this study is that Rawtype Riot customers do not prefer the type of Japanese origin jacket which is Sukajan. This caused by the color of the jacket which is famously bright and has a graphic design. By knowing these facts, company through product development can consider these factors which can be modified so that it can be accepted by customer Rawtype Riot taste.Keywords: custom culture, in-depth interview, marketing research, Apparel, exploratory research